Factors Affecting Selection of Contraceptive Methods and Its Length of Use - Erdiyan Astato; Djajadilaga Djajadilaga (Indonesian Journal of Obstetrics and Gynecology, 2015)
Objective: To evaluate the factors related to the selection of contraceptive methods and length of use on acceptors in Raden Saleh Clinic and Fatmawati General Hospital. Method: The study was a prospective observational study designs. The factors that we observed include the family planning factor (wife age, number of desired children and infertility), subjective factors (side effect experience of contraception, support from the husband/ family, and religion), objective factors (medical disorders, person helping to select contraception, family planning service centre and availability of contraceptives) and the level of motivation (level of education). All the clients who will receive contraception and meet the criteria for the research were interviewed and given questionnaires until the desired sample size is achieved. The study was conducted at the Raden Saleh Clinic and Fatmawati General Hospital. We then conducted follow-up at 3 and 6 months after the use of the contraceptive methods to assess the length of use. Result: The total number of subjects was 151 people. The average age of respondents was 31 years old, with the contraception options being IUD (67.1%), implants (17.8%), sterilization (7.2%), injectable contraception (3.9%), and oral contraception (3.9%). From all the factors studied, only the number of desired children were found to affect the selection of contraceptive methods significantly (p=0.008) in Fatmawati General Hospital, while in Raden Saleh Clinic all of the factors did not affect the selection of contraceptive method (p>0.05). We also found that all of these factors do not have a significant relationship to the length of contraceptive use (p>0.05). There were 6.6% of subjects (n=10) who switched the type of contraception. From all of them, there was a trend of switching from oral contraceptive to injectable method (33.3%) and from IUD to injectable method (66.7%). Conclusion: Only the number of desired children has an effect on the selection of contraceptive methods in Fatmawati General Hospital, while in Raden Saleh Clinic all of the factors studied do not affect in selection of contraceptive methods. Family planning factors, subjective factors, objective factors and motivation levels have no effect on the length of contraceptive use by clients at Raden Saleh Clinic and Fatmawati General Hospital. Keywords: contraception methods, factors, length of use, selection